Assembly and Chiral Memory Effects of Dynamic Macroscopic Supramolecular Helices - Yuan, Tianyu; Sun, Zhimin; Mu, Anthony U.; Zeng, Minxiang; Kalin, Alexander J.; Cheng, Zhengdong; Olson, Mark A.; Fang, Lei (Chemistry : a European journal, 2018)
Macroscopic enantiomerically pure helical supramolecular fibers are bottom‐up assembled in aqueous media from a chiral π‐electron donor template and an achiral π‐electron acceptor. The helices can be assembled to the sub‐millimeter scale with controlled handedness. These dynamic supramolecular architectures allow for a quantitative exchange of the chiral donor template with achiral analogues. During this process, a chiral memory effect was observed, affording enantiomerically pure helices composed entirely of achiral components. Macroscopic enantiomerically pure helical supramolecular fibers were bottom‐up assembled in aqueous media from a chiral π‐electron donor template and an achiral π‐electron acceptor. The helices can be assembled to the sub‐millimeter scale with controlled handedness.